Influence of Work Motivation, Work Environment, and Leadership Style on Employee Job Satisfaction at the Paser District Environmental Service - Kurniawati, Andry Listiana; Herdiana, Dian; Santosa, Agus (PT. Riset Press International, 2023)
Abstract The aim of this research is to analyze the influence of work motivation, work environment and leadership style on employee job satisfaction at the Paser Regency Environmental Service. The design in this research is quantitative descriptive research. The research population was all employees at the Paser Regency Environmental Service, totaling 156 people. The sampling technique in this research used a purposive sampling technique. The sample chosen for this research was all 82 employees with State Civil Apparatus status. In this research, the research instrument used was a questionnaire. The results of data analysis explain that the influence of the work motivation variable on the job satisfaction variable is 0.183, the influence of the work environment variable on the job satisfaction variable is 0.434, and the influence of the leadership style variable on the job satisfaction variable is 0.331. This shows that work motivation, work environment and leadership style have a positive and significant effect on employee job satisfaction. It is hoped that leaders can pay attention to employee incentives, make improvements to existing buildings, and build active communication with employees.